The Use of Graphic Programs in the Educational Process of Technical Subjects at Secondary Schools and Universities - Kučerka, Martin; Žáčok, Ľubomír; Bernát, Milan (The University of Rzeszów Publishing House, 2024)
In the era of digital transformation in education, graphic programs are becoming an indispensable tool in the educational process of technical subjects at secondary schools and universities. Their use extends beyond innovative methods of knowledge transfer and positively influences the development of students' cognitive abilities, such as spatial imagination, analytical thinking, and problem-solving. Moreover, mastering graphic programs prepares students for the demands of the current labour market in fields such as engineering, architecture, and design. This study analyses the use of graphic programs in the education process of technical subjects at secondary and higher education institutions, focusing on their specifics in the context of each educational level.
Keywords: graphic programs; technical subjects; cognitive skills; digital transformation of education